2013
DOI: 10.1037/a0031578
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial spending and well-being: Cross-cultural evidence for a psychological universal.

Abstract: This research provides the first support for a possible psychological universal: Human beings around the world derive emotional benefits from using their financial resources to help others (prosocial spending). In Study 1, survey data from 136 countries were examined and showed that prosocial spending is associated with greater happiness around the world, in poor and rich countries alike. To test for causality, in Studies 2a and 2b, we used experimental methodology, demonstrating that recalling a past instance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
348
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(385 citation statements)
references
References 138 publications
22
348
3
12
Order By: Relevance
“…We are here concerned with the simple frequency of pro-social spending, not with the amount donated. In a 133-nation study drawing upon an earlier wave of the Gallup Organization's annual global surveys than that used in the present study, Aknin, Barrington-Leigh, et al (2013) found that the proportion of persons in each nation having donated to charity during the past month correlated with nation-level wealth at r = .54. However, as noted earlier, Levine et al (2001) found helping less frequent in the richer nations in their sample.…”
Section: Wealthmentioning
confidence: 95%
“…We are here concerned with the simple frequency of pro-social spending, not with the amount donated. In a 133-nation study drawing upon an earlier wave of the Gallup Organization's annual global surveys than that used in the present study, Aknin, Barrington-Leigh, et al (2013) found that the proportion of persons in each nation having donated to charity during the past month correlated with nation-level wealth at r = .54. However, as noted earlier, Levine et al (2001) found helping less frequent in the richer nations in their sample.…”
Section: Wealthmentioning
confidence: 95%
“…A large body of research has established an association between kindness and well-being (Anik, Aknin, Norton, & Dunn, 2009;Konrath & Brown, 2013). However, much of this research has been correlationalshowing, for example, that people who spend more money on others are happier (Aknin, Barrington-Leigh, et al, 2013), or people who volunteer to help others are healthier (Jenkinson et al, 2013).…”
Section: The Consequences Of Kindnessmentioning
confidence: 99%
“…Another hypothesis found in the literature also states volunteer work to strengthen and broaden one's social relations and social relations to also be a significant predictor of happiness, health, depression, and long life (Borgonovi, 2008). While one study found the sense of awe related to peace provides an indicator of people's pro-social behaviors (Piff, Dietze, Feinberg, Stancato, & Keltner, 2015), another study supported the intercultural findings that pro-social behaviors increase well-being (Aknin et al, 2013). Individuals that show self-esteem and helpful behaviors are seen to have high levels of life satisfaction and desire to live and to experience low levels of depression, anxiety and somatization (Post, 2005).…”
Section: Social Virtuesmentioning
confidence: 58%